Exosomes Derived From Pericytes Improve Microcirculation and Protect Blood–Spinal Cord Barrier After Spinal Cord Injury in Mice - Yuan, Xiaochen; Wu, Qingbin; Wang, Peng; Jing, Yingli; Yao, Haijiang; Tang, Yinshan; Li, Zhigang; Zhang, Honggang; Xiu, Ruijuan (Frontiers in Neuroscience, 2019)
Spinal cord injury（SCI) often leads to severe and permanent paralysis and places a heavy burden on individuals, families and society. Until now, the therapy of SCI is still a big challenge for the researchers. Transplantation of mesenchymal stem cells (MSCs) is a hot spot for the treatment of spinal cord injury, but many problems and risks have not been resolved. Some studies have reported that the therapeutic effect of MSCs on spinal cord injury is related to the paracrine secretion of cells. The exosomes secreted by mesenchymal stem cells have therapeutic potential on many diseases. There are abundant pericytes which possess the characteristics of stem cell in the neurovascular unit. Due to the close relationship between pericytes and endothelial cells, the exosomes of pericytes can be uptake by endothelial cells more easily. There are fewer studies about the therapeutic potential of the exosomes derived from pericytes on spinal cord injury now. In this study, exosomes of pericytes were transplanted into the mice with SCI to study the restoration of motor function and explore the underlying mechanism. We found that the exosomes derived from pericytes could reduce pathological changes, improve the motor function, the blood flow and oxygen deficiency after SCI. In addition, the exosomes could improve the endothelial ability to regulate blood flow, protect the blood-spinal cord barrier, reduce edema, decrease the expression of HIF-1α, Bax, Aquaporin-4 and MMP2, increase the expression of Claudin-5, bcl-2 and inhibit apoptosis. The experiments in vitro proved that exosomes derived from pericytes could protect the barrier of spinal cord microvascular endothelial cells under hypoxia condition, which was related to PTEN/AKT pathway. In summary, our study showed that exosomes of pericytes had therapeutic prospects for spinal cord injury.